Efflux pump inhibitor combined with ofloxacin decreases MRSA biofilm formation by regulating the gene expression of NorA and quorum sensing. Issue 4 (19th January 2023) - Lu, Xueer; Wang, Guifeng; Xie, Yunfeng; Tang, Wenjian; Liu, Biyong; Zhang, Jing
Abstract : Carbonyl cyanide p -nitrophenylhydrazone (2e ), an efflux pump inhibitor, displayed alone or synergistic efficacy against MRSA in vitro and in vivo through regulating the gene expression of NorA and QS system. Abstract : Carbonyl cyanide p -nitrophenylhydrazone (2e ) displayed a lone or synergistic efficacy against MRSA ( RSC Adv., 2020, 10, 17854). In this work, the synergistic mechanism of 2e with ofloxacin was studied. MRSA2858 had potential for biofilm formation, and the value of MBEC of 2e alone was 0.78–1.56 μM, while that of 2e + ofloxacin was 0.39–0.78 μM. 2e combined with ofloxacin showed a synergistic anti-biofilm effect against MRSA. Efflux pump inhibitor 2e can better bind to NorA protein. After MRSA2858 was treated with 2e of 1/2MIC (0.78 μM) and ofloxacin of 1/8MIC (0.097 μM), the transcript levels of efflux genes ( norA ) and quorum-sensing (QS) regulatory genes ( agrA, sarA, icaA, hla ) were substantially down-regulated, and alpha-hemolysin (Hla) was inhibited by 99.15%. 2e combined with ofloxacin was more effective than 2e alone in reducing bacterial load in vivo . All in all, efflux pump inhibitor 2e enhanced the bactericidal activities of antibiotics through regulating the gene expression of NorA and QS system.